Sistemática e filogenia de Trechaleidae (Araneae, Lycosoidea) - Silva, Estevam Luís Cruz da (2012)
The first revised genus of Trechaleidae was Trechalea Thorell, 1890, by Carico (1993), after this revision, the systematic of this spider family started to be know for the Neotropical region. The cladistic analysis of the Trechaleidae genera used 64 taxa and 79 characters, including all genera formerly assigned to Trechaleidae Simon, 1890, all exemplars of all families currently placed in higher lycosoids sensu Griswold (1993), and an array of potential Lycosoid outgroups, resulted in a single most parsimonious tree of 380 steps (FIT = 56.08, K = 6, Ci = 0.26, Ri = 0.65). This analysis suggests that Psechridae is sister to an Oxyopidae + Senoculidae lineage. Ctenidae, only represented here by Ancylometes Bertkau, 1880 showed to be more related to Pisauridae. The subfamily Rhoicininae Simon, 1898 is sister group of Lycosidae and is promoted to family rank (Rhoicinidae, New Status). Shinobius orientalis (Yaginuma, 1967) is confirmed as a true member of Rhoicinidae and closely related to Heidrunea Brecovit & Höfer, 1994. Neoctenus Simon, 1897 also does not fall within Trechaleidae and is transferred to Zoridae. The family Trechaleidae is now divided in three subfamilies: Dosseninae (Dossenus Simon, 1898, New Subfamily), Enninae (Enna O. Pickard-Cambridge, 1897, New Subfamily) and Trechaleinae Simon, 1890. The cladogram shows detailed resolution within the newly delimited Trechaleidae. Two new genera, Paradyrines gen. nov. and Neotrechalea gen. nov., are described and illustrated for the first time. Caricelea Silva & Lise, 2007 is synonymized with Enna O. Pickard- Cambridge, 1897. Trechalea Thorell, 1869 is sister to the clade fromed by Syntrechalea F. O. Pickard-Cambridge, 1902. The Rhoicininae Simon, 1898 was recently removed from Trechaleidae Simon, 1869 and promoted to family rank based on the results of a morphological study made by Silva et al. (2011). The family was revised and illustrated. Rhoicinidae is composed by four genera: Barrisca Chamberlin & Ivie, 1936, Heidrunea Brescovit & Höfer, 1994, Rhoicinus Simon, 1898 and Shinobius Yaginuma, 1991. Barrisca nannella Chamberlin & Ivie, 1936 (type-species) and B. kochalkai Platnick, 1978 are redescribed and illustrated. The male of B. kochalkai and a new species from Peru are described and illustrated for the first time. The types of Heidrunea Brescovit & Höfer, 1994 (H. arijana Brescovit & Höfer, 1994, H. irmleri Brescovit & Höfer, 1994 and H. lobrita Brescovit & Höfer, 1994) were photographed and illustrated. The genus Rhoicinus comprises 10 known species and all known species are redescribed and illustrated. Rhoicinus weyrauchi Exline, 1960 is a junior synonym of R. wapleri Simon, 1898. Rhoicinus cashiari sp. nov. is described and illustrated from material collected in Peru. The monotypic genus Shinobius Yaginuma, 1991 is redescribed and illustrated. Maps with the distribution of the representatives of the family are presented. Since 2008, 14 papers were published based on review papers and several new species were described and illustrated from Central and South America. The genera Enna O. P.-Cambridge, 1897 and Dyrines Simon, 1903 were revised by Silva et al. (2008) and Carico & Silva (2008), respectively. After the revision of Enna, in 2008, 13 new species were described. A new species of Dyrines was described by Silva & Lise (2010). Syntrechalea F. O. Pickard-Cambridge, 1902 was revised by Carico (2008) and after that work, three new species were described by Silva & Lise (2008, 2010) (two from Northern Brazil and one from Colombia). Based on material from Peru, two new species of Caricelea Silva & Lise, 2007, were proposed. The male of Hesydrus caripito Carico, 2005 and a new species of Enna (Enna echarate Silva & Lise, 2009) were described. Dossenus was revised by Silva et al. (2007), and the male of Dossenus guapore Silva, Lise & Carico, 2007 and a new species from Northern Brazil (Pará) were described. The male of Paratrechalea longigaster Carico, 2005 was described and illustrated and new records of the distribution of Paratrechalea were registered to Brazil. The last trechaleid genus to be revised was Paradossenus F.O.P.- Cambridge, 1903. Carico & Silva (2010) described and illustrated six new species and Silva & Lise (2011) described the female of Paradossenus macuxi from Roraima, Brazil. And the nuptial gift behavior of the male of Trechalea amazonica F. O. Pickard- Cambridge was recorded for the first time to Pará, Brazil.